2016
DOI: 10.1109/tvcg.2016.2518158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Virtual Human Appearance Fidelity on Emotion Contagion in Affective Inter-Personal Simulations

Abstract: Realistic versus stylized depictions of virtual humans in simulated inter-personal situations and their ability to elicit emotional responses in users has been an open question for artists and researchers alike. We empirically evaluated the effects of near visually realistic vs. non-realistic stylized appearance of virtual humans on the emotional response of participants in a medical virtual reality system that was designed to educate users in recognizing the signs and symptoms of patient deterioration. In a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(43 citation statements)
references
References 29 publications
2
40
0
1
Order By: Relevance
“…Similarly, Chittaro et al (2014) found that fear and skin conductance could be induced by providing high-fidelity portrayals of character harm (e.g., rendering of blood) during an aircraft evacuation simulation. However, Volonte et al (2016) found that lower fidelity cartoon and sketch-based rendering algorithms elicited greater negative emotions (e.g., anger, fear, and guilt) than a high-fidelity rendering algorithm, when interacting with a deteriorating virtual patient.…”
Section: Emotionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, Chittaro et al (2014) found that fear and skin conductance could be induced by providing high-fidelity portrayals of character harm (e.g., rendering of blood) during an aircraft evacuation simulation. However, Volonte et al (2016) found that lower fidelity cartoon and sketch-based rendering algorithms elicited greater negative emotions (e.g., anger, fear, and guilt) than a high-fidelity rendering algorithm, when interacting with a deteriorating virtual patient.…”
Section: Emotionmentioning
confidence: 94%
“…While some journalists may worry about how the CG-based simulations of mobile VR experiences impact the emotions of their audience, prior research indicates that emotions can not only be elicited with CG (Chittaro et al, 2014), but that lower fidelity visual realism may elicit more emotions than high-fidelity visual realism (Volonte et al, 2016). Also, CG-based mobile VR is more likely to induce the sense of body ownership than 360° videos because the viewer's body can be easily represented in the virtual world.…”
Section: Cg-based Mobile Vrmentioning
confidence: 99%
“…Even though the field of VR-based research geared toward clinical application is not a novelty, there is still no direct correspondence of presence and related factors to the level of induced emotional arousal. Although a reinforcing role of realism on the behavioral response is noted in Slater et al (2009) and in full body avatars in Gutiérrez-Maldonado et al (2009), in Volonte et al (2016) an opposite effect is reported. Furthermore, compared to alternatives.…”
Section: Introductionmentioning
confidence: 88%
“…Jun et al [16] highlighted the significance of not only appearance and behavior but also nonverbal communication and affective components towards the quality of user experience. The relationship between rendering/display fidelity of virtual human models and emotional reactions is investigated in [32].…”
Section: From Voice-only To Immersive Vpamentioning
confidence: 99%